The capital market in Nigeria - Olukole, R. A. (Lagos, Nigeria : R.A. Olukole, 2002)
The book focuses on the Nigerian stock market. It covers the origin, history, operations of the Nigerian stock market from inception to 1998.
Includes bibliographical references (p. 308-309) and index.
lje 12/07/16
Loans
Keywords: Capital market; Stock exchanges; Nigeria